Uncertainty Analysis of the Effect of Modulus of Elasticity on Seismic Performance of Concrete Quay Wall - Mehdi Kouchaki; Majid Pasbani Khiavi; Mortaza Ali Ghorbani (Numerical Methods in Civil Engineering)
This paper investigated the sensitivity of the seismic performance of quay wall system to changes in the modulus of elasticity of the body concrete Monte Carlo probabilistic analysis, which is a new method for parametric study and sensitivity analysis. Monte Carlo method presents an appropriate solution to consider a specified range for various parameters effective in analyzing. The ANSYS software which is based on finite element method is applied for analysis considering fluid-structure interaction effect. In the uncertainty analysis, modulus of elasticity of the quay wall body concrete is a parameter indicating the stiffness and strength of body in design of concrete structures and has been selected as input variable parameter. Additionally, the maximum displacement of the crest and the maximum tensile principal stress in critical point of the body has been selected as output variables. The model is analyzed in time domain by applying the horizontal and vertical components of El Centro earthquake. Finally, the effect of the modulus of elasticity on the maximum responses at each stage is shown as sensitivity curves. According to the results, an optimal value is obtained for the modulus of elasticity of quay wall concrete to ensure system safety.